An investigation of nitrogen cycling processes in a coastal fynbos ecosystem in the South Western Cape Province, South Africa - Stock, William David (Department of Biological Sciences, 2016)
The Cape Floral Kingdom, known locally as "fynbos", is of great scientific and aesthetic interest as well as being economically important as a water source zone, as a source of flowers for the cut flower industry and as a recreation area. Sound ecological knowledge is required in order to manage and conserve fynbos because the extent of this unique, species-rich, endemic flora has been drastically reduced. Nutrients, in particular nitrogen and phosphorus, have been identified as being of crucial importance in the structure and functioning of fynbos ecosystems because of the nutrient poor substrates upon which this vegetation type exists. This study has concentrated on the following aspects of the nitrogen cycle which are considered to be important in describing the functioning of a coastal fynbos ecosystem: a) The nitrogen status of soils supporting coastal fynbos. b) The forms of nitrogen and the seasonal changes in nitrogen concentrations in these soils. c) The influence of fire disturbance on nitrogen form and concentration in these soils. d) An investigation of the nitrogen mineralization process in these soils in relation to control by physical factors, successional age of the stand and the impact of fire on this process. e) The uptake and utilization of different forms of nitrogen by characteristic species of fynbos vegetation. f) The importance of internal recycling of nitrogen as an adaptation to the low nutrient soils of the area. g) The role of atmospheric inputs of nitrogen to the ecosystem, in particular the importance of this source in replacing nitrogen lost during recurrent fires.